Perancangan Bahan Ajar Digital Akuntansi Keuangan di SMK Swasta di Kota Batam Pada Pandemi COVID-19 - Budi Chandra; Siti Mahmudah (Universitas Internasional Batam, 2021)
Since the outbreak of the pandemic caused by the COVID-19 virus in Indonesia, many aspects have been affected, one of which is in the field of education. With the virus, the government is setting up distance learning activities or online. This problem causes a lack of digital teaching materials owned by the school. So researchers designed digital financial accounting teaching materials at private vocational schools in Batam City during the covid-19 pandemic. The digital teaching materials that the researchers made were financial accounting modules and power point. With the hope that the resulting teaching materials are able to assist teachers in carrying out the teaching and learning process, and make it easier for students to understand the material presented. Digital teaching materials will be implemented by the school and evaluation of the assessment of teaching materials will receive positive feedback so that they are suitable for use.